Biogeochemical and Molecular Signatures of Anaerobic Methane Oxidation in a Marine Sediment - Thomsen, Trine R. (American Society for Microbiology, 2001)
Anaerobic methane oxidation was investigated in 6-m-long cores of marine sediment from Aarhus Bay, Denmark. Measured concentration profiles for methane and sulfate, as well as in situ rates determined with isotope tracers, indicated that there was a narrow zone of anaerobic methane oxidation about 150 cm below the sediment surface. Methane could account for 52% of the electron donor requirement for the peak sulfate reduction rate detected in the sulfate-methane transition zone. Molecular signatures of organisms present in the transition zone were detected by using selective PCR primers for sulfate-reducing bacteria and for Archaea. One primer pair amplified the dissimilatory sulfite reductase (DSR) gene of sulfate-reducing bacteria, whereas another primer (ANME) was designed to amplify archaeal sequences found in a recent study of sediments from the Eel River Basin, as these bacteria have been suggested to be anaerobic methane oxidizers (K. U. Hinrichs, J. M. Hayes, S. P. Sylva, P. G. Brewer, and E. F. DeLong, Nature 398:802–805, 1999). Amplification with the primer pairs produced more amplificate of both target genes with samples from the sulfate-methane transition zone than with samples from the surrounding sediment. Phylogenetic analysis of the DSR gene sequences retrieved from the transition zone revealed that they all belonged to a novel deeply branching lineage of diverse DSR gene sequences not related to any previously described DSR gene sequence. In contrast, DSR gene sequences found in the top sediment were related to environmental sequences from other estuarine sediments and to sequences of members of the genera Desulfonema, Desulfococcus, and Desulfosarcina. Phylogenetic analysis of 16S rRNA sequences obtained with the primers targeting the archaeal group of possible anaerobic methane oxidizers revealed two clusters of ANME sequences, both of which were affiliated with sequences from the Eel River Basin.